Integration of information literacy in the Library and Information Science curriculum in Mozambique - Manhique, Ilidio Lobato E.; Casarin, Helen de Castro Silva [UNESP] (Univ Estadual Campinas - Sistema Bibliotecas, 2025)
Introduction: Information literacy is a set of processes, knowledge, skills and learning that are essential in contemporary society, as it enables people to be aware and critical in the production, use and sharing of information. Aim: The objective of this research was to investigate the inclusion of the topic of information literacy in the curriculum of librarianship courses located in Mozambique. Methodology: The research was developed in two stages: documentary research that consisted of the analysis of the curricula of the Escola Superior de Jornalismo (ESJ) and the Escola de Comunica & ccedil;& atilde;o e Artes of the Universidade Eduardo Mondlane, Mozambique. Interviews were also conducted with 22 students in the third and fourth years of these courses. Results: The results indicated the absence of specific subjects and contents that use the nomenclature of information literacy. Implicit elements were identified in subjects of the courses that cover contents that can potentially develop aspects of information literacy. Conclusion: It is essential to make information literacy explicit in Mozambican librarianship courses, in the form of disciplines and other specific activities, since these courses are responsible for qualifying people with skills and knowledge for planning and implementing educational programs in libraries and other formal and informal environments.
Keywords: Information literacy; Librarianship; Education; Mozambique